2022
DOI: 10.1021/acs.analchem.2c03550
|View full text |Cite
|
Sign up to set email alerts
|

Offline Coupling of Asymmetrical Flow Field-Flow Fractionation and Capillary Electrophoresis for Separation of Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) play important roles in cell-to-cell communications and carry high potential as markers targeted in disease diagnosis, prognosis, and therapeutic development. The main obstacles to EV study are their high heterogeneity; low amounts present in samples; and physical similarity to the abundant, interfering matrix components. Multiple rounds of separation and purification are often needed prior to EV characterization and function assessment. Herein, we report the offline coupling of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…To identify the optimal injection volume of the collected AF4 fractions for LVSS/CE, we obtained the F2 fraction from the separation of 10 μL pooled human serum and injected it with various conditions: 1× F2: the nonstacking condition at 100 mbar for 10 s; 10×, 15×, and 20× LVSS: the stacking conditions at 100 mbar for 100, 150, and 200 s, respectively. This fraction was found in our previous work to elute EVs in diameters of 100–200 nm with relatively higher purity than F1 and F3 . We found that with 1× F2 EVs (Figure A) and 10× LVSS (Figure B), EVs and LDL were successfully resolved, and their migration times were consistent with the corresponding standards.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…To identify the optimal injection volume of the collected AF4 fractions for LVSS/CE, we obtained the F2 fraction from the separation of 10 μL pooled human serum and injected it with various conditions: 1× F2: the nonstacking condition at 100 mbar for 10 s; 10×, 15×, and 20× LVSS: the stacking conditions at 100 mbar for 100, 150, and 200 s, respectively. This fraction was found in our previous work to elute EVs in diameters of 100–200 nm with relatively higher purity than F1 and F3 . We found that with 1× F2 EVs (Figure A) and 10× LVSS (Figure B), EVs and LDL were successfully resolved, and their migration times were consistent with the corresponding standards.…”
Section: Resultssupporting
confidence: 72%
“…This fraction was found in our previous work to elute EVs in diameters of 100−200 nm with relatively higher purity than F1 and F3. 19 We found that with 1× F2 EVs (Figure 2A) and 10× LVSS (Figure 2B), EVs and LDL were successfully resolved, and their migration times were consistent with the corresponding standards. But more peak broadening and fronting, later elution, were observed with longer LVSS times (Figure 2B), indicating sample overloading, which also reduced the separation resolution between EV and LDL (Figure 2C).…”
Section: ■ Results and Discussionsupporting
confidence: 55%
See 3 more Smart Citations